PENGARUH OTONOMI AUDIT DAN AMBIGUITAS PERAN TERHADAP KINERJA AUDITOR - Galih Chandra Kirana (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2022)
The results showed that the Auditor's Work Results as measured by the level of Role Ambiguity did not have a positive and significant effect on Auditor Performance and Audit Autonomy as measured by the results of the work completed by the auditors had a positive and significant effect on Examiner Performance.